2015
DOI: 10.1007/s00384-015-2257-z
|View full text |Cite
|
Sign up to set email alerts
|

Compression anastomotic ring-locking procedure (CARP) is a safe and effective method for intestinal anastomoses following left-sided colonic resection

Abstract: Our results indicate that the novel suture-less CARP is a safe and effective method for creating colonic anastomoses. Further studies are warranted in larger patient populations to compare CARP head-on-head with stapled and/or hand-sewn colonic anastomoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“… 4 , 30 Recent compression anastomosis systems can be distinguished by their implant halves’ interlocking mechanism and the principle of permanent pressure application into form fit, shape memory, and magnet-based implants. While the compression rings in form fit-based systems (eg, AKA-2 (Seidel, Medipool, Friedrichsthal, Germany), 4 , 29 , 30 , 32 Valtrac, “Biofragmentable Anastomotic Ring” (BAR) (Sherwood-Davis & Geck, St. Louis, MO, USA) 4 , 6 , 12 , 30 , 33 , 34 and RapAn 4 , 35 ) consist of dimensionally stable materials (Metal, Polyetherketone or Polyglycolic acid), shape memory-based implants use the temperature-dependent shape changing effect of Nickel Titanium Alloy (NITINOL) for pressure application (eg, “Compression Anastomosis Clip” (CAC) (NiTi Alloys Technologies, Ltd., Netanya, Israel), “Compression Anastomosis Ring” (NiTi CAR or ColonRing) (novoGI Inc. formerly NiTi Surgical Solutions Ltd., Netanya, Israel)). 30 , 36–40 Both principles require mechanical closure mechanisms for the connection of the ring elements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 30 Recent compression anastomosis systems can be distinguished by their implant halves’ interlocking mechanism and the principle of permanent pressure application into form fit, shape memory, and magnet-based implants. While the compression rings in form fit-based systems (eg, AKA-2 (Seidel, Medipool, Friedrichsthal, Germany), 4 , 29 , 30 , 32 Valtrac, “Biofragmentable Anastomotic Ring” (BAR) (Sherwood-Davis & Geck, St. Louis, MO, USA) 4 , 6 , 12 , 30 , 33 , 34 and RapAn 4 , 35 ) consist of dimensionally stable materials (Metal, Polyetherketone or Polyglycolic acid), shape memory-based implants use the temperature-dependent shape changing effect of Nickel Titanium Alloy (NITINOL) for pressure application (eg, “Compression Anastomosis Clip” (CAC) (NiTi Alloys Technologies, Ltd., Netanya, Israel), “Compression Anastomosis Ring” (NiTi CAR or ColonRing) (novoGI Inc. formerly NiTi Surgical Solutions Ltd., Netanya, Israel)). 30 , 36–40 Both principles require mechanical closure mechanisms for the connection of the ring elements.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that compression anastomoses can potentially be compared with conventional and staple suturing techniques in terms of safety and surgical outcome, or in some cases even produce better results. 32 , 35 , 36 , 38 , 77 , 86 , 95 , 96 Especially, the expulsion of the compression implants enabling a foreign-body-free healing process, leading to less scarring, deserves notice. In their meta-analysis, however, Slesser et al concluded that there were no advantages with regard to postoperative complications in favor of compression anastomoses 15 and our meta-analysis also did not provide any evidence of superiority.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006 the NiTi CAR 27 ring was introduced, which should guarantee consistent compression by nitinol springs. Newer methods are the CARP (compression anastomotic ring-locking procedure) [ 92 ] and the so-called Magnamosis by magnetic rings [ 93 ]. At a first glance, compression anastomoses could have advantages due to constant pressure distribution, avoiding local nutrient and blood undersupply, lack of gap formation, and foreign body reactions to staples or sutures.…”
Section: Comparison Of Conventional Techniquesmentioning
confidence: 99%
“…Recently, a novel compression anastomotic device called CARP (compression anastomotic ring-locking procedure) has been introduced [ 28 ]. CARP allows not only a stapel-free anastomosis, but has also four built-in catheters enabling measurement of the intraoperative anastomotic contact pressure (ACP) and postoperative monitoring of potential leakage [ 28 , 29 ]. This makes CARP a unique device with capacity to quantify anastomotic integrity.…”
Section: Introductionmentioning
confidence: 99%
“…This makes CARP a unique device with capacity to quantify anastomotic integrity. A previous study showed that CARP was effective and safe in left-sided colo-colic anastomoses in patients undergoing resection of the sigmoid colon [ 29 ]. However, the CARP device is limited to open surgery and has now been modified in order to be used in minimally invasive procedures and for transanal rectal anastomoses.…”
Section: Introductionmentioning
confidence: 99%